Performance Measurement of the Info BMKG Application Using the Information Technology Infrastructure Library (ITIL) V.4 Framework - Budi Susilo; Joko Triloka (Journal of Technology and Informatics (JoTI), 2026)
The Meteorology, Climatology, and Geophysics Agency (BMKG) provides information to the public through the Info BMKG mobile application. This app delivers data on earthquakes, early warnings, weather, climate, and other meteorological topics. Observations, interviews, and user reviews from the Google Play Store highlight several issues. These include an unstructured display, inaccurate location information, and delays in earthquake notifications. To address these, the application’s performance was evaluated using the ITIL V4 management practices. The assessment collected questionnaire data from internal users, stakeholders, and the public. Analysis showed an average maturity level of 4.56, with the largest gap (0.76) in service desk management. Recommendations for improvement were provided for each management activity. These aim to ensure best practices in the application. With these findings, the Info BMKG app is seen as applying continuous improvement practices based on ITIL V4, supporting IT integration, and enhancing organizational quality, efficiency, and adaptability.